1994
DOI: 10.1111/j.1365-2958.1994.tb01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted mutagenesis of the phospholipase D gene results in decreased virulence ofCorynebacterium pseudotuberculosis

Abstract: The chromosomal gene encoding the phospholipase D from Corynebacterium pseudotuberculosis (biovar ovis) isolate Whetten 1 was replaced with an allele containing a nonsense mutation. The virulence of the mutant strain (W1.31r1) and the isogenic parental strain were then compared by inoculation of goats. The wild-type strain caused abscessation at the site of infection, which then spread to the regional lymph node, while W1.31r1 had a reduced ability to establish a primary infection and was incapable of dissemin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(71 citation statements)
references
References 24 publications
1
65
0
5
Order By: Relevance
“…A SMaseD-deficient mutant of C. pseudotuberculosis is unable to disseminate from the site of inoculation (13), and a popular theory is that vascular hyperpermeability caused by SMaseD, shown here to be likely a result of LPA production, aids in the escape of bacteria into the lymphatic system and subsequent spread to regional lymph nodes (44).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A SMaseD-deficient mutant of C. pseudotuberculosis is unable to disseminate from the site of inoculation (13), and a popular theory is that vascular hyperpermeability caused by SMaseD, shown here to be likely a result of LPA production, aids in the escape of bacteria into the lymphatic system and subsequent spread to regional lymph nodes (44).…”
Section: Resultsmentioning
confidence: 99%
“…C. pseudotuberculosis causes lymphadenitis in animals but is also pathogenic for humans, while C. ulcerans and A. hemolyticum are pathogens of pharyngitis and other human infections (11); in no case is the molecular basis for virulence known (12). The SMaseD from C. pseudotuberculosis, also named SM-specific phospholipase D (PLD), is an essential virulence determinant that contributes to the persistence and spread of the bacteria within the host (13). The Loxosceles and C. pseudotuberculosis SMases D have the same molecular mass (31-32 kDa) and share about 30% sequence similarity (see "Results").…”
mentioning
confidence: 99%
“…This analog protein, though inactive, still had immunological activity [49]. Hodgson et al [51] and McNamara et al [68] used site-specific mutagenesis to produce pld mutants that had reduced ability to establish infection and were unable to disseminate in sheep and goats.…”
Section: Generation Of Mutantsmentioning
confidence: 99%
“…A similar mutagenesis study using serum sensitivity as the readout and pneumonia as the validation step identified phospholipase D (PLD) as a bona fide virulence factor (47). Interestingly, PLD www.intechopen.com is also associated with virulence in Neisseria gonorrhoeae (48) and Corynebacterium pseudotuberculosis (49). Hence this enzyme could be used as a drug target for the design of novel antimicrobials.…”
Section: Virulence Factors Of a Baumanniimentioning
confidence: 99%